Assessment Of Seed Cake And Fermented Slurry Of Jatropha Seed As Bio-Fertilizer - Mohammed M.O.; Abdalrhaman M.S. (Nusa Putra University, 2018)
The objectives of this study were to evaluate the seed cake and fermented slurry of Jatropha seed as bio- fertilizer. The chemical analyses showed that the seed cake has 6.3% nitrogen, 0.9% phosphorus and 1.2% potassium. While fermented slurry showed 6.65% nitrogen, 5.3% phosphorus and 0.71% potassium. The Fermentation increased nitrogen content from 6.3 to 6.65 and Phosphorus from 0.9 to 5.3 while the potassium was decreased from 1.2 to 0.71. It is obvious that fermentation of seed cake resulted in substantial increase of phosphorus. The seed cake and fermented slurry of Jatropha seed were tested as bio-fertilizer. Similar doses of both Seed cake and fermented slurry were used (5, 10 and 20t/hectare). Both components were tested using sorghum plants. The bio-fertilizers were applied 30 days after sowing. The higher doses of the seed cake resulted in complete loss of the sorghum plants. There is no difference between the control and the lower doses. On the other hand the fermented slurry caused an increase in number of leaves stem diameter and plant height. It could be concluded that the toxicity of seedcake can be removed by fermentation. Microbiological investigation indicated that the microorganisms involved in the fermentation process were Bacillus and Lactobacillus bacteria.